A relation between the characteristic stellar ages of galaxies and their intrinsic shapes. (June 2018) - van de Sande, Jesse; Scott, Nicholas; Bland-Hawthorn, Joss; Brough, Sarah; Bryant, Julia; Colless, Matthew; Cortese, Luca; Croom, Scott; d′Eugenio, Francesco; Foster, Caroline; Goodwin, Michael; Konstantopoulos, Iraklis; et al.
Abstract Stellar population and stellar kinematic studies provide unique but complementary insights into how galaxies build-up their stellar mass and angular momentum1–3 . A galaxy's mean stellar age reveals when stars were formed, but provides little constraint on how the galaxy's mass was assembled. Resolved stellar dynamics4 trace the change in angular momentum due to mergers, but major mergers tend to obscure the effect of earlier interactions5 . With the rise of large multi-object integral field spectroscopic surveys, such as SAMI6 and MaNGA7, and single-object integral field spectroscopic surveys (for example, ATLAS3D (ref.8 ), CALIFA9, MASSIVE10 ), it is now feasible to connect a galaxy′s star formation and merger history on the same resolved physical scales, over a large range in galaxy mass, morphology and environment4, 11, 12 . Using the SAMI Galaxy Survey, here we present a combined study of spatially resolved stellar kinematics and global stellar populations. We find a strong correlation of stellar population age with location in the (V /σ, $${\boldsymbol{ε}}_{{\boldsymbol{e}}}$$ ϵ e ) diagram that links the ratio of ordered rotation to random motions in a galaxy to its observed ellipticity. For the large majority of galaxies that are oblate rotating spheroids, we find that characteristic stellar age follows the intrinsic ellipticity of galaxies remarkably well. Α combined study of spatially resolved stellar kinematics and global stellar populations with the SAMI Galaxy Survey finds a strong correlation between the characteristic stellar population age of a galaxy and its intrinsic ellipticity.